Per- and perfluoroalkyl substances alternatives, mixtures and liver function in adults: A community-based population study in China. (May 2022) - Liu, Jiao-Jiao; Cui, Xin-Xin; Tan, Ya-Wen; Dong, Peng-Xin; Ou, Yan-Qiu; Li, Qing-Qing; Chu, Chu; Wu, Lu-Yin; Liang, Li-Xia; Qin, Shuang-Jian; Zeeshan, Mohammed; Zhou, Yang; et al.
Graphical abstract: Abstract: Experimental evidence has shown that per- and polyfluoroalkyl substances (PFAS) alternatives and mixtures may exert hepatotoxic effects in animals. However, epidemiological evidence is limited. This research aimed to explore associations of PFAS and the alternatives with liver function in a general adult population. The study participants consisted of 1, 303 adults from a community-based cross-sectional investigation in Guangzhou, China, from November 2018 to August 2019. We selected 13 PFAS with detection rates > 85% in serum samples and focused on perfluorooctane-sulfonic acid (PFOS), perfluorooctanoic acid (PFOA) and their alternatives [6:2 chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFESA), 8:2 Cl-PFESA, and perfluorohexanoic acid (PFHxA)] as predictors of outcome. Six liver function biomarkers (ALB, ALT, AST, GGT, ALP, and DBIL) were chosen as outcomes. We applied regression models with restricted cubic spline function to explore correlations between single PFAS and liver function and inspected the combined effect of PFAS mixtures on liver by applying Bayesian kernel machine regression (BKMR). We discovered positive associations among PFAS and liver function biomarkers except for ALP. For example, compared with the 25th percentile of PFAS concentration, the level of ALT increased by 12.36% (95% CI: 7.91%, 16.98%) for ln-6:2 Cl-PFESA, 5.59% (95% CI: 2.35%, 8.92%) for ln-8:2 Cl-PFESA, 3.56% (95% CI: −0.39%, 7.68%) for ln-PFHxA, 13.91% (95% CI: 8.93%, 19.13%) for ln-PFOA, and 14.25% (95% CI: 9.91%, 18.77%) for ln-PFOS at their 75th percentile. In addition, higher exposed serum PFAS was found to be correlated with greater odds of abnormal liver function. Analysis from BKMR models also showed an adverse association between PFAS mixtures and liver function. The combined effect of the PFAS mixture appeared to be non-interactive, in which PFOS was the main contributor to the overall effect. Our findings provide evidence of associations between PFAS alternatives, PFAS mixtures, and liver function in the general adult population.